INCREASING AWARENESS OF WASTE SORTING THROUGH THE PROVISION OF FACILITIES AND COMMUNITY-BASED EDUCATION IN MANDIRANCAN VILLAGE - Rois Harliyanto; Muhammad Rafli Miftahudin; Syifa Aulia Nugraha; Fitri Dwi Jayanti; Panji Muhammad Ramdan; Azmi Azzahra; Azka Zakiyah; Aliya Rohmah Aliyati; Nur Khopipah Endah; Mochamad Fachrurozi; Syifa Maliyatul Husna; Fairuz Azhar Pratama; Rama Yuda Nur Prayoga (Ann Publisher, 2026)
Background: Waste management problems still become a challenge in the community, especially due to low awareness of waste sorting. In Mandirancan Village, most of the community still mixes organic and inorganic waste and has not utilized the inorganic waste that has economic value. Aim: This research aims to increase community awareness of waste sorting by providing inorganic waste bin facilities and accompanying community-based education. Methods: This activity used a Participatory Action Research (PAR) approach, with data collection techniques including observation, interviews, and documentation of 20 respondents. The activity stages included coordination, construction of waste bins, socialization, and evaluation of facility utilization. Results: The results showed an increase in several indicators, namely waste sorting practices from 12% to 48%, community understanding of waste types from 25% to 68%, and the utilization of waste bin facilities from 8% to 52%, based on the results of observation and interviews Conclusion: The program for the provision of inorganic waste bins accompanied by education is proven to improve community understanding and behavior in waste management, although the changes that occurred are not yet evenly distributed and still require a process of habituation Implication: Further efforts are needed, including ongoing education, community assistance, and the development of a community-based waste management system, to ensure behavior changes are consistent and sustainable.